Phenomenological coefficients in solid-state diffusion: an Introduction - Murch, Graeme E.; Belova, Irina V. (Diffusion Fundamentals, 2005)
In this review, which is intended as an introduction to the subject, we introduce the phenomenological transport coefficients in solid-state diffusion and discuss their structure and physical meaning. Next, we discuss the Darken, the Manning, the Moleko, Allnatt and Allnatt and the Heumann expressions which relate the phenomenological coefficients to the (measurable) tracer diffusion coefficients. Finally, we discuss the relationships (sum-rules) among the phenomenological coefficients themselves in randomly mixed systems and note their applicability for simplifying collective diffusion problems.